Compartment syndrome and regional anaesthesia: Critical review - Klucka, Jozef; Stourac, Petr; Stouracova, Alena; Masek, Michal; Repko, Martin (Biomedical papers, 2017)
Acute compartment syndrome (ACS) is a potential orthopaedic/traumatology emergency. Without prompt, precise diagnosis and immediate treatment with surgical decompressive fasciotomy it can lead to neurological dysfunction and disability. The role of regional anaesthesia (RA) in patients at risk for ACS/ and in those with developed ACS is controversial. The aim of this critical review was to answer the question, whether regional anaesthesia can delay the diagnosis. The authors use an evidence-based approach to discuss these high risk patients in considering RA as a method of choice for effective analgesia. To the date of data collection, there was no single case report identified where RA alone led to delay in ACS diagnosis and surgical treatment. In four clinical cases, epidural analgesia can be associated with delayed ACS diagnosis. Frequent clinical evaluation and breakthrough pain despite a functional RA in combination with intracompartment pressure measurement remains the keystone of recommended management for patients at risk of ACS.
Keywords: compartment syndrome; regional anaesthesia; peripheral nerve block/blockade